EVALUASI WAKTU TUNGGU PELAYANAN RESEP RACIKAN POLI SPESIALIS ANAK PASIEN BPJS DI RUMAH SAKIT MEDIKA DRAMAGA BOGOR - Muhammad Afqary; Dewi Wiyanti; Inda Firliah (Jurnal Farmamedika (Pharmamedika Journal), 2018)
Pharmacy services are one of the health services in hospitals that are expected to meet minimum service standards. So that one way to meet minimum service standards is to adjust the accuracy of pharmaceutical services with minimum service standards set by the government. The waiting time for concoction services is the time for patients to submit their prescriptions to receive concoction drugs with a minimum standard set of ≤ 60 minutes. The purpose of this study was to find out the factors that caused the length of prescription services for BPJS poly pediatric concoctions at the Medika Dramaga Hospital, Bogor. This research is a survey research using a quantitative approach and supported by qualitative. The results showed that the average waiting time for concoction prescription services at the Dramaga Medika Hospital in Bogor with a sample of 134 sheets of pediatrician's prescription concoction of 62.29 minutes consisted of: powder, capsules, syrup and ointment. This has not fulfilled the Decree of the Minister of Health No.129 / Menkes / SK / II / 2008.